Protocol for developing a model to promote the mental health of nurses caring for mental healthcare users at mental health institutions in Limpopo province, South Africa. - Annikie V Hobyane; Hilda N Shilubane; Tinyiko N Rikhotso (PLoS ONE)
The nurses as front liners caring for mental health care users (MHCUs) at mental health institutions are susceptible to adverse physical and psychological effects as a result of hostile behaviors of mentally ill patients. Most nurses suffer from stress that is caused by management's lack of support, working overtime, lack of recognition by supervisors, and lack of skills and knowledge on how to handle aggressive mental health care users. The present study aims to develop a model to promote the mental health of nursing staff providing care to individuals with mental disorders at mental health institutions. Phase 1, the empirical face, will employ a qualitative, exploratory, and descriptive design focusing on nurses' experiences caring for MHCUs and their views on improving their mental health. Information will be gathered using unstructured individual interviews with nurses purposefully sampled at selected mental health institutions. The study will apply procedures to safeguard trustworthiness and moral principles during the study. Phase 2 will focus on developing a model, and in phase 3, the developed model will be validated. The findings of the study will determine recommendations.